Malaria transmission potential of Anopheles gambiae s.l. in indoor residual spraying areas with clothianidin 50 WG in northern Benin - Esdras Mahoutin Odjo; Mathilde Tognidro; Renaud Govoetchan; Antoine Abel Missihoun; Gil Germain Padonou; Juvenal Minassou Ahouandjinou; Bruno Akinro; Zinsou Come Koukpo; Filémon T. Tokponnon; Armel Djenontin; Clement Agbangla; Martin C. Akogbeto (Tropical Medicine and Health, 2024)
Abstract The study objective was to assess the frequency of the kdr-L995F and ace-1 G280S genetic mutations in Anopheles gambiae s.l. mosquitoes and examine their ability to transmit Plasmodium falciparum in areas where indoor residual spraying (IRS) was implemented with Clothianidin 50 WG. The study was conducted in six communes in the Alibori and Donga departments of which four were IRS-treated and two were untreated and served as control. Post-IRS monthly samples of adult mosquitoes were collected in study communes using human landing catches (HLC). An. gambiae s.l. specimens were processed to detect kdr-L995F and ace-1 G280S mutations via PCR as well as Plasmodium falciparum infectivity through CSP ELISA. Our data revealed a high and similar allelic frequency for the kdr-L995F mutation in both treated and control communes (79% vs. 77%, p = 0.14) whilst allelic frequency of the ace-1 G280S mutation was lower across the study area (2–3%, p = 0.58). The sporozoite rate was 2.6% and 2.4% respectively in treated and untreated communes (p = 0.751). No association was found between Plasmodium falciparum infection in Anopheles gambiae s.l. vectors and carriage of kdr-L995F and ace-1 G280S mutations regardless of genotypes. The study findings underline the need for an integrated approach to malaria control, combining different control methods to effectively target transmission. Regular monitoring of insecticide resistance and genetic mutations is essential to guide control strategies.